Determinasi loyalitas penyewa: Lokasi, kualitas layanan, kepuasan, dan persepsi harga - Triyono Arief Wahyudi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to analyze the influence of location and perceived service quality on tenant loyalty in an office park building in Jakarta, with tenant satisfaction as a mediating variable and perceived price as a moderating variable. A total of 140 respondents participated in this research, consisting of company representatives involved in decision-making regarding office space leasing. The study employed multiple linear regression to examine relationships among variables, and hypotheses were tested using the same method. The findings reveal that: (a) building location has a significant effect on tenant satisfaction; (b) perceived service quality significantly influences tenant satisfaction; (c) tenant satisfaction has a significant impact on tenant loyalty; and (d) perceived price significantly moderates the relationship between tenant satisfaction and loyalty. These results indicate that a strategic location and high-quality service contribute positively to tenant satisfaction, which, in turn, enhances tenant loyalty. Furthermore, perceived price strengthens the relationship between satisfaction and loyalty, highlighting its importance in sustaining long-term tenant relationships